Model Pembelajaran Snowball Throwing Di Sekolah Dasar - Hery Setiyawan (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This research is apreliminary research that contains efforts to implement the snowball throwing learning model at the elementary level, especially in grade 4. This study also aims to determine student responses to the application of the snowball throwing learning model at the elementary school level. This study used a research design with the "One Shot Case Study" design, namely research conducted by giving certain treatment to research subjects, in this case the snowball throwing learning model. The data obtained were analyzed using research methods for students. In this study the authors used a data collection technique in the form of a questionnaire technique. The questionnaire used in this research is a student learning motivation questionnaire. The results of this study indicate that students' responses to learning using the snowball throwing model received a positive response with a percentage of 88.43%.